STATED PREFERENCES FOR CONSUMPTION OF GARAVOLLI FROM THE MEYHANE MANAGERS' POINT OF VIEW - Demir, Ayse; Altun, Özlem; Elidemir, Servet Nasifoglu; Girgen, Mete (My University, 2024)
Gastronomy tourism is a tourism variety with a high economic return that presents the cultural cuisine identity of a region to tourists with all stages of food, various experiences and activities. It is important that foods reflecting cultural identity act together with stakeholders such as festivals, feasts, fairs, congresses and restaurants where local food and beverages are prepared and served, which are among the important factors in destination marketing. In this context, the preparation, cooking and presentation of garavolli as an island appetizer, in restaurants with meyhane concept, and consumer preference were investigated. In this research, qualitative method was adopted; semistructured interview technique was used. The research participants consist of 20 voluntary meyhane operators in Famagusta and İskele districts. As a result of the research, it is seen that garavolli is a very important product in establishing a cultural bond with local and foreign visitors as a popular appetizer type produced and served in meyhanes of Cyprus. For those who first experienced garavolli, it was seen that the demand could increase when it was served with sauces such as fried chicken and breadcrumbs; It has been understood that if it is marketed, it can be a destination element that attracts tourists in countries such as France, Spain and Portugal, which consume this food in the world.
Keywords: Gastronomy; Meyhane; Garavolli